Dispersed PM10 Microspheres from Coal Fly Ash: Fine Fraction Separation, Characterisation, and Glass–Ceramic Preparation - Elena V. Fomenko; Galina V. Akimochkina; Natalia N. Anshits (Molecules, 2025)
Developing resource-efficient technologies for producing ceramic materials with specific properties and performance characteristics is one of the most important tasks in modern materials science. As natural resources face depletion, the use of anthropogenic wastes, including fly ash from coal combustion, for the development of new compositions and the production of ceramics with an improved microstructure is of particular significance. The use of PM10 fly ash microspheres in ceramic production will help to reduce particulate matter emissions. In this study, fine narrow fractions of PM10 microspheres were successfully separated from coal fly ash using aerodynamic and magnetic separation. Glass–ceramic materials with a homogeneous microstructure, an open porosity of 0.4–37%, a compressive strength of 5–159 MPa, and acid resistance of up to 99.9% were obtained using narrow fractions. The materials obtained are promising for application as highly porous ceramics, effective microfiltration membranes, and fine-structured technical ceramics, which can be used in installations operating in aggressive media and/or at high temperatures. The ceramic membranes were characterised by high liquid permeability values up to 1194 L·m−2·h−1·bar−1. Filtration tests showed that the retention coefficient for dispersed microsilica particles with dav = 1.9 μm is 0.99.